Barriers to and facilitators of hormonal and long-acting reversible contraception access and use in the US among reproductive-aged women who use opioids: A scoping review - Elizabeth Charron; Jacqueline Kent-Marvick; Tyler Gibson; Eliza Taylor; Kelsey Bouwman; Gelina M. Sani; Sara E. Simonsen; Rebecca H. Stone; Jennifer E. Kaiser; Mary M. McFarland (Preventive Medicine Reports, 2023)
Existing research has found that women who use opioids (WWUO) experience challenges to hormonal and long-acting reversible contraception (HC-LARC) access and use. Facilitators of such use are unclear. We conducted a scoping review to comprehensively map the literature on barriers to and facilitators of HC-LARC access and use in the United States among reproductive-aged WWUO. In accordance with the JBI Manual of Evidence Synthesis, we conducted literature searches for empirical articles published from 1990 to 2021. Independent reviewers screened references, first by titles and abstracts, then by full-text, and charted data of eligible articles. We coded and organized HC-LARC barriers and facilitators according to a four-level social-ecological model (SEM) and categorized findings within each SEM level into domains. We screened 4,617 records, of which 28 articles focusing on HC-LARC (n = 18), LARC only (n = 6), or testing an intervention to increase HC-LARC uptake (n = 4) met inclusion criteria. We identified 13 domains of barriers and 11 domains of facilitators across four SEM levels (individual, relationship, community, societal). The most frequently cited barriers and facilitators were methods characteristics, partner and provider relations, transportation, healthcare availability and accessibility, cost, insurance, and stigma. Future studies would benefit from recruiting participants and collecting data in community settings, targeting more diverse populations, and identifying neighborhood, social, and policy barriers and facilitators. Reducing barriers and improving equity in HC-LARC access and use among WWUO is a complex, multifaceted issue that will require targeting factors simultaneously at multiple levels of the social-ecological hierarchy to effect change.